家庭不同手足數的國中生學習成就差異之探討 - 張芳全(Fang-chung Chang) (School Administrators, 2024)
This study used data from the Keelung City Junior High School Student Learning Status Survey Database to explore the differences in academic achievement among families with different sibling numbers in the fields of Chinese, English, mathematics, nature, health and physical education, society, arts and humanities, and comprehensive activities. There were 1,586 students in this analysis that had families with one, two, three and four siblings, with 160, 825, 450 and 151 children respectively. The conclusions showed that the academic achievements of different sibling numbers in the eight fields were different. In families with two children, the academic achievement was the best in eight fields, followed by three children, and the only child. In both cases, four children have the worst academic performance. After post hoc comparative analysis, the academic performance of the only child in the family in English, mathematics, and natural sciences was significantly lower than that of the two children in the family,